Performance Evaluation of Market Timers: Theory and Evidence - Kane, Alex; Marks, Stephen Gary (Journal of Financial and Quantitative Analysis, 1988)
Previous investigators have shown that the Sharpe measure of the performance of a managed portfolio may be flawed when the portfolio manager has market timing ability. Herein we develop the exact conditions under which the Sharpe measure will completely and correctly order market timers according to ability. The derived conditions are necessary, sufficient, and observable. We compare these derived conditions to empirical estimates of actual market conditions and find that, under typical market conditions, the practice of using quarterly portfolio return data will frequently result in a failure of the Sharpe measure to order timers according to ability. We show, however, that such failures can be greatly reduced by more frequent sampling of managed portfolio returns.